Profil Lagu untuk Anak Usia Dini - Rina Wulandari (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2021)
Music is positioned as an empty time filler in the lesson plan and there is still the fact that music is also only for entertainment. Meanwhile, in several studies it has been proven that music has a supporting role in stimulating children's development. The research method used is qualitative, narrative type, scientific report type. Sources of research data are field observations, children's development books, music books for children, research articles about the effectiveness of the music field. The validity of the data was done by matching the facts in the field with related books and articles. The results of the study: 1) Language development in early childhood has appeared at the age of 18 months, namely children behave in arranging two words which will increase with the age of the child, 2) Rhythm at sukat 2/4 is highly recommended to use a tempo of 80, 3) using ambitus specifically for children, the safest type is tessitura, 4) using main chords, 5) using literal science, sequences, and two-part song forms.